Regulation of the anti-senescence factor, TBX2, by the UV stress signalling pathway and the mitotic cyclin dependent kinases - Abrahams, Amaal (Division of Medical Biochemistry, 2017)
The T-box gene family has achieved great prominence in the field of developmental biology because its members have been demonstrated to play important roles in embryonic development and mutations within several T-box genes are associated with a number of human congenital diseases. Several lines of evidence have also implicated members of the T-box gene family in cell cycle regulation and in cancer. Importantly, the highly related T-box factors, Tbx2 and Tbx3, can suppress senescence through repressing the cyclin dependent kinase inhibitors, p21wAF11 c1P118011 and p19ARF. Both Tbx2 and Tbx3 have also been linked to several cancers primarily because their expression levels have been found to be deregulated in these cancers. However, despite the pivotal role that members of the T-box family play in a wide variety of biological processes, very little is known about the biochemical pathways that regulate their levels and transcriptional activity. In view of the detrimental consequences resulting from altered levels of T-box proteins, as seen both in developmental disorders and in certain cancers, the need to identify such pathways is important. The aim of this study was therefore to identify kinases that phosphorylate and regulate the levels and activity of Tbx2 with the view to understanding its role in cell cycle regulation and cancer. This study shows that the p38 stress mitogen-activated protein kinase, and the mitotic cyclin A/Cdk2 and cyclin B1/Cdk1, are direct regulators of Tbx2 both in vitro and in vivo. It is possible that Tbx2 and Tbx3 may contribute towards the oncogenic process through their anti-senescence function, especially since a dominant negative form of Tbx2 induces senescence in melanoma cells overexpressing Tbx2. However, very little is known about whether Tbx2 is indeed regulated during replicative- or stress-induced senescence. In this study, using a breast cancer cell line known to overexpress Tbx2, the Tbx2 protein is shown to be specifically phosphorylated by the p38 kinase in response to stress induced by ultraviolet irradiation. Using site-directed mutagenesis and in vitro kinase assays, serine residues 336, 623 and 675 in the Tbx2 protein were identified as p38 target sites. These sites are also shown to be phosphorylated in vivo. Importantly, western blotting, immunofluorescence and reporter assays reveal that this phosphorylation leads to increased Tbx2 protein levels, predominant nuclear localisation of the protein, and an increase in the ability of Tbx2 to repress the p21wAF11 c/P118011 promoter. These results show, for the first time, that the ability of Tbx2 to repress the p21 gene is enhanced in response to a stress-induced senescence pathway. This leads to a better understanding of the anti-senescence function of Tbx2. The ability of Tbx2 to function as an anti-senescence factor, as well as its altered regulation being associated with certain cancers, suggests that"its levels may need to be tightly regulated during the cell cycle. Indeed, the Tbx2 protein was previously shown to be regulated during the various phases of the cell cycle, peaking at G2. The changes in the Tbx2 protein levels did not match changes in Tbx2 mRNA levels, suggesting that the protein may be regulated by posttranslational modifications such as phosphorylation. This study shows that the phosphorylation status of Tbx2 is regulated during the cell cycle with levels of phosphorylation peaking in G2 and M, in mouse and human cells respectively. Phosphorylation was shown to be specifically mediated by the mitotic kinases as demonstrated in experiments when the mitotic kinase inhibitor, olomoucine, was included. This study provides data to suggest that Tbx2 may be regulated differently during the cell cycle in mouse and human cells. Using site-directed mutagenesis and in vitro kinase assays, Tbx2 was found to be specifically phosphorylated at serine residues 192 and 336 by cyclin A/Cdk2 and serine residues 336 and 342 by cyclin 81/Cdk1. These sites are also targets for phosphorylation in vivo since mutating them altered the phosphorylation status ofTbx2. Moreover, both cyclin A and 81 were shown to bind Tbx2 in vitro and in vivo and the minimal region required for binding was mapped to its DNA-binding domain. Importantly, immunofluorescence demonstrates that the Tbx2 protein localises specifically to the nucleus at G2; this translocation was shown to be blocked in the presence of olomoucine. Furthermore, western blot analyses and reporter assays showed that pseudo-phosphorylation by cyclin 81/ Cdk1, but not cyclin A/Cdk2, leads to increased Tbx2 protein levels and an increase in the ability of Tbx2 to repress the p21wAFtiCIPt!Sou promoter. These results disclose, for the first time, that phosphorylation by cyclin A/Cdk2 and cyclin 81/Cdk1 of the Tbx2 protein regulates its activity. This data provide additional evidence to support a role for Tbx2 in the G2 and/or M phase of the cell cycle.